EXPERIENCE OF EXPOSURE FROM RADON HEALTH STUDY - V. M. Shubik; E. V. Ivanov; V. N. Kashin; V. A. Kolobyanin (Радиационная гигиена)
The article summarizes and analyses the results of research work conducted by the authors collective on high radon concentration effects on mine workers from the tungsten ore mine and population of the Akchatau settlement located in the Dzhezkazgan region of Kazakstan around this mine. Heightened morbidity rate for lung cancer, respiratory tract diseases is being revealed. Clinical examination found out pathological changes among the population of settlement, which can be linked with the radiation exposure: cataracts, abnormal gestation courses. Immunological investigations revealed some causes of discovered pathological changes: tissue immunodepression ofrespiratory tract, autoimmune processes to the lung antigens at respiratory system pathology.